2012
DOI: 10.1109/jsen.2011.2135343
|View full text |Cite
|
Sign up to set email alerts
|

Sensing With Slow Light in Fiber Bragg Gratings

Abstract: On the edge of the bandgap in a fiber Bragg grating (FBG) narrow peaks of high transmission exist at frequencies where light interferes constructively in the forward direction. In the vicinity of these transmission peaks, light reflects back and forth numerous times across the periodic structure and experiences a large group delay. Since the sensitivity of a phase sensor to most external perturbations is proportional to the reciprocal of group velocity, in these slow-light regions the sensitivity of an FBG is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…2 to its measured group delay, we estimate the rate of absorption for light in the FBG region to be 5.4 1.7 × 10 7 s −1 . Assuming that the same absorption applies to wavelengths of light passing through the 1.2 cm FBG without interacting with the grating, we estimate the broadband, nonresonant absorption induced in the fiber core by the grating writing process to be α 0.25 0.17 m −1 (0.057 0.040 dB∕cm), which is in keeping with FBGs with similar Δn in SMF-28 [10]. Figure 4(a) shows a close up of the six lowest-order transmission peaks simulated by the transfer matrix method with (black) and without (red) this estimated absorption.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…2 to its measured group delay, we estimate the rate of absorption for light in the FBG region to be 5.4 1.7 × 10 7 s −1 . Assuming that the same absorption applies to wavelengths of light passing through the 1.2 cm FBG without interacting with the grating, we estimate the broadband, nonresonant absorption induced in the fiber core by the grating writing process to be α 0.25 0.17 m −1 (0.057 0.040 dB∕cm), which is in keeping with FBGs with similar Δn in SMF-28 [10]. Figure 4(a) shows a close up of the six lowest-order transmission peaks simulated by the transfer matrix method with (black) and without (red) this estimated absorption.…”
mentioning
confidence: 61%
“…Experimentally these fine resonant structures were first reported in 1993 [6] and have been shown to exhibit group delays of several nanoseconds [10]. In this work we investigate the relationship between the group delay and FIE of these resonant modes, which could be used to enhance nonlinear optical phenomena in fiber [5].…”
mentioning
confidence: 91%
“…Thus, optical fiber sensors have been used for pressure sensing [1]; strain sensing [2]; gyroscopes [3]; acoustic sensing [4], [5]; and temperature sensing [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been theoretically and experimentally proved that the extreme dispersion of slow light can lead to an enhancement of the spectral sensitivity of interferometers 4 . The role of slow light in gyroscopes has also been theoretically investigated 5 and the possibility to use fiber Bragg gratings to realize ultrasensitive strain sensors has been experimentally proved 6 . Recent works 7,8 have theoretically demonstrated that BeerLambert-Bouguer (BLB) absorption can be increased while light transmits through a special kind of microstructured photonic crystal (PC) cuvette.…”
Section: Introductionmentioning
confidence: 99%